MANAJEMEN DANA ZAKAT, INFAK, DAN SEDEKAH UNTUK PEMBERDAYAAN MASYARAKAT: STUDI KASUS PADA LAZISMU TANAH BUMBU - Junaidi; Budiman, Mochammad Arif; Nurhidayati (FKIP Unswagati, 2025)
This study examines the management of Zakat, Infak, and Sedekah (ZIS) funds for community empowerment at Lazismu Tanah Bumbu through a descriptive qualitative approach. The research specifically investigates the implementation of four core management functions, planning, organizing, implementing, and controlling, in the institution’s ZIS fund management practices. Data was collected through semi-structured interviews, institutional documentation, and a review of relevant literature. The analytical process employed data reduction, data presentation, and conclusion drawing to capture the practical application of these management functions within the organizational context. The findings reveal that Lazismu Tanah Bumbu has applied the four management functions in a reasonably effective manner. Planning is conducted periodically, guided by the organization’s flagship programs. The organizational structure is well-aligned to support efficient program implementation. Fundraising and distribution activities are carried out with a strong emphasis on transparency and accountability, while oversight is ensured by the Sharia Supervisory Board. However, the study also identifies the need for more robust fundraising strategies to address the observed decline in infak and sedekah contributions, as well as to expand the coverage and impact of the institution’s beneficiary programs. This research contributes to the discourse on faith-based philanthropic management by highlighting best practices and areas for improvement in the operationalization of ZIS fund management for sustainable community empowerment. Keywords: management of ZIS, zakat, infak, alms, lazismu